Profiles. The Way MA Students Perceive Professional Accountants and Managers - Victoria Bogdan; Tomina Săveanu; Olimpia Iuliana Ban; Dorina Nicoleta Popa (Journal of Accounting and Management Information Systems (JAMIS), 2016)
Nowadays, the accountant's and business manager's image in society is an increasingly debated subject in the literature. The existing stereotypes in accounting developed in relation with the national context affect the students' attitude towards accounting (Albu et al., 2012). This study aimed to design the profiles of professional accountants and managers in the perception of 106 MA students. We used the questionnaire and the projective research techniques. The exploratory factor analysis, revealed three distinct profiles of accountants: liberal and independent, statutory and advisor professional accountant, and two profiles of managers: confident and conservative. Only the profile of statutory professional accountant is explained by experience and education and there is a positive correlation between the scale of professional judgment and this profile. We found that the higher the score for statutory professional accountant the stronger the opinion that the correctness of professional judgment is reflected in a relevant information. The association done by the MA students with a book fits the greatest extent to the liberal and independent accountant and for the MA students who supported the confident manager profile, the association is largely congenial with a color.
Keywords: M41; A14; Z13; 650; accountant; manager; MA students; association technique; judgment and decision making